Demystifying AI for the enterprise : a playbook for business value and digital transformation - Natarajan, Prashant (New York : Productivity Press, 2021)
Artificial Intelligence in its various forms - machine learning, chat-bots, robots, agents, etc. - is increasingly being seen as a core component of enterprise business workflow and information management systems. The current promise and hype around AI are being driven by software vendors, academic research projects, and startups. However, we posit that the greatest promise and potential for AI lies in the enterprise with its applications touching all organizational facets. Increasing business process and workflow maturity coupled with recent trends in cloud computing, datafication, IoT, cyber security, and advanced analytics, there is appreciation that the challenges of tomorrow cannot be solely addressed with today's people, processes, and products. A recent Gartner article supports our contention that AI is essential because it "promises to solve problems organizations could not before because it delivers benefits that no humans could legitimately perform." There is still considerable mystery, hype, and fear about AI. A considerable amount t of current discourse focuses on a dystopian future - with adversity impacted individuals/employees/society. Such opinions, with understandable fear of the unknown, don't consider the history of human innovation, current state of business/technology, or the primarily augmentative nature of tomorrow's AI. Our book demystifies AI for the enterprise. Our journey takes the reader from the basics (definitions, state of the art, etc.) to a multi-industry journey, and concludes with validated expert advice on everything an organization and its people must do to succeed. Along the way, we also debunk myths, provide practical pointers, and include best practices with appropriate vignettes. In summary, AI brings to enterprises capabilities that promise new ways by which professionals can address both mundane and interesting challenges more efficiently, effectively, and collaboratively (with humans). The opportunity for tomorrow's enterprise is to augment existing teams and resources with the power of AI in order to gain competitive advantage, discover new business models, establish or optimize new revenues and achieve better customer/user satisfaction.
OCLC-licensed vendor bibliographic record.
Keywords: Artificial intelligence -- Industrial applications; Business enterprises -- Data processing; BUSINESS & ECONOMICS / Leadership; COMPUTERS / Artificial Intelligence